The Effectiveness of Embryological Development in Fly Larvae (Diptera Sp) Against Several Types of Meat - Elis Yana; Safitri Safitri; Afifah Luftiah Tantri; Febri Ramadhani Hasibuan (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2023)
The purpose of this study was to determine the development of embryos in flies on several media, namely chicken meat, fish meat, and shrimp. This research was conducted in November 2022 in Laud Dendang Village, Kec. Percut Sei Tuan, Deli Serdang Regency, with data obtained from direct observation. The approach used in this research is quantitative in nature from the results of observing the life cycle of Diptera sp flies measured and observed in daily records, and the observations are made in tabular form, and the type of research conducted is descriptive in nature. This study aims to determine the development of embryos in flies on several media, namely chicken meat, fish meat, and shrimp. In this study using tools and materials that are easily available. using three media, namely the first media using 50 grams of chicken meat, then using 50 grams of fish meat media, and the third using 50 grams of shrimp meat media. The results of this study indicate that the stages from adult flies and producing eggs take 48 hours. Then the stages from eggs to larvae take 48 hours and then the stages from larvae to chicks take 72 hours and among the three media the most suitable media for flies are chicken meat because chicken meat is thicker and has sufficient moisture for the growth of flies.